Performance verification of audio converter integrated circuits - Shankar, Nat Udaya. (2008)
Performance verification of semiconductor devices plays a vital role in the semiconductor industry. Every component manufactured has to be tested before being shipped to the customer. At one million dollars for a typical test system, testing becomes one of the most expensive operations. Scaling down the test cost has become the main target for test engineers but at the same time fault coverage has to be maintained. In this dissertation a newly emerging test methodology based on digital signal processing is investigated for developing performance verification solutions of audio converter integrated circuits. It is shown that these solutions for production testing are far superior to solutions using traditional techniques when the performance of every device coming out of a production line has to be verified.